PENGARUH PARENTAL BURNOUT (KELELAHAN ORANG TUA) IBU TERHADAP EMOTIONAL REGULATION (REGULASI EMOSI) ANAK USIA 4-6 TAHUN DI KOTA GRESIK - Anggi Triwulandhari; Wulan Patria Saroinsong; Muhammad Reza; Suharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Emotional regulation is an essential ability in early childhood that influences children’s social and psychological development. However, this ability is still developing and is highly dependent on parental support. One factor that may affect children’s emotional regulation is parental burnout, a condition of emotional exhaustion caused by prolonged parenting demands. This study aims to examine the effect of maternal parental burnout on the emotional regulation of children aged 4–6 years. This study employed a quantitative approach with a correlational design. The research was conducted in Gresik, with 400 mothers of children aged 4–6 years as participants. Data were collected using questionnaires, including a parental burnout scale (23 items, score range 0–6) and an emotional regulation scale (15 items, score range 1–4). The instruments were developed based on relevant theoretical dimensions. Data analysis was performed using simple linear regression. The results showed that maternal parental burnout has a negative and significant effect on children’s emotional regulation (R = 0.675; R² = 0.456; p < 0.05). This indicates that higher levels of parental burnout are associated with lower emotional regulation in children. Parental burnout contributed 45.6% to the variance in emotional regulation, while 54.4% was influenced by other factors. In conclusion, maternal psychological well-being plays an important role in the development of children’s emotional regulation. It is recommended that parents receive adequate social and psychological support to reduce burnout and optimize children’s emotional development.